India : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in India during 1996-98. After three successive years of growth more than 7 percent, growth of slowed to an estimated 5 percent in 1997/98. The slowdown predates the Asian crisis, and its proximate causes are a decline in agricultural output and weak industrial sales. Weaker investment appears to be a major factor behind the industrial slowdown. The balance of payments continued to improve in 1997/98, despite a widening in the current account deficit to 1 1\2 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet